Lipase purification. - Ling, Tau Chuan (2010)

(untitled)
This invention provides an aqueous micellar two-phase system (AMTPS) medium for lipase purification from Bukholderia sp. wherein the medium includes a 0.25 to 1.0 wt. % relative to total AMTPS of a chloride salt, 0.5 to 1.0 wt. % relative to total AMTPS of a thiocyanate salt and 24 wt. % relative to total AMTPS of a nonionic triblock copolymer (PEO-PPO-PEO) with a number-average molecular weight (Mn) of 2800. The AMTPS is comprised of a single nonionic Pluronic L81, potassium chloride, potassium thiocyanate and buffer. The invention also provides a method of lipase purification using the said aqueous micellar two-phase system (AMTPS) medium for lipase purification from Burkholderia sp. wherein the steps include (a) adding 50 wt. % relative to total AMTPS of unclarified Burkholderia sp. culture into the AMTPS; (b) separating the AMTPS from step (a) into primary bottom phase; (c) replacing the primary top phase with an equal volume of thiocyanate salt; (d) subjecting the primary bottom phase to back-extraction with the replaced primary top phase to form secondary top and secondary bottom phase; (e) recycling the surfactant from the secondary top phase; and (f) recovering purified lipase from the secondary bottom phase. Lipases are purified in the primary micellar bottom phase, whereas other protein contaminants are retained in the primary aqueous top phase. Lipases are then recovered in a newly formed secondary aqueous bottom phase by the addition of potassium thiocyanate into the primary bottom phase. The recycled surfactant is reused in the preparation of new AMTPS.